PENGARUH DRY HEAT TREATMENT TERHADAP DAYA SIMPAN BENIH CABAI RAWIT (Capsicum frutescens L.) - Raka, I Gusti Ngurah; Astiningsih, Anak Agung Made; Nyana, I Dewa Nyoman; Siadi, I Ketut (Journal of Agricultural Science and Biotechnology; Volume 1, No 1, Tahun 2012)
The aims of this experiment were to compare the shelf life of chili pepper seeds given dry heat treatment (DHT) and non dry heat treatment (NT). This experiment was conducted in Laboratory of Seed Technology Faculty of Agriculture, Udayana University. The study consisted of two experiments that attempt to use lots of chili seeds treated with dry heat treatment (DHT) and experimental use a lot of chili seeds without dry heat treatment (NT). This experiment uses a randomized completely design (RCD) with 10 replications.  Each type of chili pepper seeds tested each power shelf with 10 replications. Storage treatment performed at room temperature, which consists of non-storage (T0), storage for 2 weeks (T2), storage for 4 weeks (T4), storage for 6 weeks (T6) and storage for 8 weeks (T8). Thus, for each lots of chili pepper there are 50 experimental units. Treatment until 8 weeks of storage time did not affect the viability and vigor of pepper seeds either DHT or NT with value up to 80%, so they do not affect seed longivity.  The dry heat treatment (DHT) showed the values of seed and seedling vigor are higher compared to that of no dry heat treatment (NT).
Keywords: Chili Pepper, Seed Viability, Seedling Vigor, Seed Longivity